1955
DOI: 10.1113/jphysiol.1955.sp005400
|View full text |Cite
|
Sign up to set email alerts
|

The effect of steroids on the maintenance of pregnancy in the spayed rat*

Abstract: Marshall & Jolly (1905 a, b) were the first to report that removal of the ovaries from the rat early in pregnancy was followed by foetal loss, although the duration of pregnancy when the rats were spayed is unknown. Subsequently, a number of workers have carried out similar experiments at different stages of pregnancy with or without removal of some of the foetuses (Selye, Collip & Thomson, 1935;Haterius, 1936;McKeown & Zuckerman, 1938;Zeiner, 1943).In all this work, the number offoetuses present in the rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1955
1955
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Based on previous reports, dosing of progestogen treatments was based upon the efficacy to sustain pregnancy. 39,[44][45][46][47][48] At about 8 and 24 hours after treatment (days 16.5 and 17 postbreeding), 3 to 5 mice were killed, a segment of reproductive tract including the cervix was excised and processed as described previously. Reproductive tracts from 4 untreated pregnant mice on the morning of day 15 postbreeding served as additional pretreatment or sham-operated controls near the peak in systemic P and softening during pregnancy.…”
Section: Experiments 2: Pr Agonists Block Ovx-induced Preterm Cervix Remodelingmentioning
confidence: 99%
“…Based on previous reports, dosing of progestogen treatments was based upon the efficacy to sustain pregnancy. 39,[44][45][46][47][48] At about 8 and 24 hours after treatment (days 16.5 and 17 postbreeding), 3 to 5 mice were killed, a segment of reproductive tract including the cervix was excised and processed as described previously. Reproductive tracts from 4 untreated pregnant mice on the morning of day 15 postbreeding served as additional pretreatment or sham-operated controls near the peak in systemic P and softening during pregnancy.…”
Section: Experiments 2: Pr Agonists Block Ovx-induced Preterm Cervix Remodelingmentioning
confidence: 99%
“…Hoet (1954) described human and rabbit foetal death, associated with excess adrenal steroids which reduce placental glycogen and penetrate to the amniotic fluid. In rats, Alexander, Frazer & Lee (1955) found that deoxycortone acetate protected foetuses from the results of oophorectomy. Our finding that acclimatization was the most effective protective measure against resorption (groups Y and Z) lends support to this theory, since adrenal steroid mobilization almost certainly takes place during heat acclimatization (Conn, 1949).…”
mentioning
confidence: 99%
“…Various workers (Marshall & Jolly, 1905;Selye, Collip & Thompson, 1935;Haterius, 1935Haterius, , 1936Zeiner, 1943;Alexander & Frazer, 1954;Alexander, Frazer & Lee, 1955) have shown that removal of both ovaries from the pregnant rat is usually followed by loss of the majority of the foetuses, unless the operation takes place very late in pregnancy. Haterius (1936), Zeiner (1943) and Alexander & Frazer (1954) all noted distortion of the foetuses.…”
mentioning
confidence: 99%
“…The rats had their abdomens opened under ether anaesthesia at the 15th day of pregnancy, and the ovaries removed by a technique already described (Alexander et al 1955). At the same time, a longitudinal incision was made in the uterine muscle over certain conceptuses, care being taken to avoid puncturing the amniotic sac.…”
mentioning
confidence: 99%